Ponatinib: a miracle or a disaster in chronic myeloid leukemia - Pal, Ayan; Panja, Buddhadev; Dutta, Trayambak; Subhrojyoti, Bhowmick; Nath, Sarmila; Bhattacharjee, Sipra (International Journal of Basic & Clinical Pharmacology, 2017)
Chronic myeloid leukemia (CML), the most common myeloproliferative disorder, occurring due to balanced reciprocal translocation between chromosome 9 and 22 and resulting in a chimeric oncogene called breakpoint cluster region-abelson (BCR-ABL) whose protein product has tyrosine kinase activity, causes uncontrolled proliferation of the myeloid cells. Although, imatinib, the first-generation tyrosine kinase inhibitor (TKI) achieved an extremely high response rate, some patients developed resistance to it. Thus, second-generation TKIs such as nilotinib, dasatinib, bosutinib were developed which proved very useful, till the emergence of T315I point mutation which occurs in the BCR-ABL gene and renders CML resistant to previous TKIs. Ponatinib, a third generation TKI approved by the United States Food and Drug Administration (FDA), showed great promise as it was effective even against T315I point mutation. However, a recent increase in the incidence of blood clots observed in patients taking ponatinib has resulted in FDA temporarily suspending all trials, marketing and distribution of the drug. Hence, whether ponatinib evolves as a miracle or disaster for the patients of CML is yet to be answered.